Support in everyday activities with a home-based electronic memory aid for persons with memory impairments. - Boman I; Bartfai A; Borell L; Tham K; Hemmingsson H (Disability & Rehabilitation: Assistive Technology, 2010)
Purpose. The purposes of this study was to examine the possibilities of a home-based electronic memory aid with sensors for persons with memory impairments, as support to carry out everyday activities in their own home environments. Method. The method involved a single-subject study with a multiple baseline AB design. Five participants identified three activities each that they usually forget to carry out. An electronic memory aid with individually spoken reminders was installed in the participant's home. There were automatic computer registrations of completed activities during the study phase of 12 weeks. Assessments of functioning and quality of life (QoL) were conducted before and after the intervention and at follow-up after 2 months. Results. Four participants improved in completing most of the self-chosen activities when the electronic memory aid was used. Performance and satisfaction with performance and QoL improved, but there was no memory function improvement. There were technical problems with the aid, which had a negative effect for users. Conclusions. Electronic memory aids have a large potential for supporting persons with cognitive impairments. It is important to conduct follow-up afterwards, because the use of an aid and the need of support change over time and put high demands on technical reliability of the electronic memory aid.